Nephropathies in civilization diseases - Czekalski, Stanisław (Przewodnik Lekarza/Guide for GPs, 2008)
Obesity, metabolic syndrome, diabetes mellitus type 2 and primary arterial hypertension are considered as diseases whose incidence increases in parallel with civilization development due to unfavourable changes of lifestyle. There is also an increase in incidence of chronic kidney diseases associated with these causes and an increase in the number of patients needing renal replacement therapy. It is necessary to introduce nephroprotective procedures in civilization diseases, which permit effective reduction of the progression of renal involvement.